Quantile hedging - Hans Föllmer; Peter Leukert (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
In a complete financial market every contingent claim can be hedged perfectly. In an incomplete market it is possible to stay on the safe side by superhedging. But such strategies may require a large amount of initial capital. Here we study the question what an investor can do who is unwilling to spend that much, and who is ready to use a hedging strategy which succeeds with high probability.
urn:nbn:de:kobv:11-10056479
Keywords: G10; G12; G13; D81; 330; Hedging; superhedging; Neyman Pearson lemma; stochastic volatility; value at risk